Successful implementation of an automated electronic support system for patient safety monitoring: The alemtuzumab in multiple sclerosis safety systems (AMS3) study. (July 2019) - Reddel, Stephen W; Barnett, Michael H; Riminton, Sean; Dugal, Tej; Buzzard, Katherine; Wang, Chenu Tim; Fitzgerald, Fiona; Beadnall, Heidi N; Erickson, Diane; Gahan, David; Wang, Daniel; Ackland, Toby; et al.
Background: Alemtuzumab is a highly effective treatment for relapsing-remitting multiple sclerosis (MS) but requires ongoing pathology monitoring for autoimmune adverse effects. The Alemtuzumab in MS Safety Systems (AMS3) study evaluated the implementation of an automated pathology-monitoring system. Objectives: To develop an efficient automated clinical decision support system (CDSS) to electronically prompt and track pathology collection and to provide prescribers and patients with customised alerts of abnormal results for identified risks. Methods: A total of 10 patients with relapsing-remitting MS treated with alemtuzumab were enrolled to test the system. Standard care laboratory monitoring was performed and compared to the performance of the CDSS. Results: The automated CDSS, an integrated patient smartphone application and an additional pre-screening tool were all successfully developed. Compliance with pathology monitoring was 96.7%. The automated analysis of pathology results was significantly faster than standard care neurologist review ( p < 0.001). The system correctly identified and alerted abnormalities, including one case of immune thrombocytopenia (ITP) while the treating neurologist was on leave, enabling prompt treatment of serious adverse events. During the course of the study, the CDSS was deployed throughout Australia. Conclusion: We successfully developed automated pathology monitoring with a CDSS, demonstrating real-world benefits of high compliance and timely alerting of important results.